Investigation of immunovascular polymorphisms and intersections in psoriasis - Urganci, Buket; Acikbas, Ibrahim; Er, F (Indian journal of dermatology, 2019)
Background: Psoriasis is a chronic, inflammatory skin disease. The etiology of the disease is unknown. It is a polygenic and multifactorial disease, which interacts with genetic and environmental factors. Genetic factors (polymorphism/mutation) can alter the immune system and normal physiologically functioning keratinocytes to pathological or predisposition levels. Aims: We aimed to investigate psoriasis at a different and novel window by searching for vascular and immunological variations and intersections in psoriasis. We investigated the main vascular and hypoxic controlling factors, which are vascular endothelial growth factor (VEGF) and hypoxia inducible factor 1 alpha (HIF-1α), as well as immunological and serotonergic factors, such as TNF-α, IL-10, and 5HT2A, which could connect each other to the pathogenesis of psoriasis. Subjects and Methods: Nine single nucleotide polymorphisms (SNPs) in five genes were genotyped by mini-array format in 300 subjects: VEGF (rs2010963, rs833061, and rs1570360), HIF-1α (rs11549465), TNF-α (rs361525, rs1799964, and rs1800629), IL-10 (rs1800896), and 5HT2A (rs6311). Results: An association was found between rs1800629 (TNF-α) and Type I psoriasis, and rs833061 (VEGF) and Type II psoriasis. Haplotype analysis suggests that the coexistence of the polymorphisms rs1799964 (TNF-α), rs2010963 (VEGF), rs833061 (VEGF), and rs6311 (5HT2A) may be a protective factor for psoriasis. Conclusion: Our results suggest that the vascular component of the studied vasculo-immunologic variation is more relevant in the pathogenesis of psoriasis.